Análise crítica do discurso sobre a democracia racial em Casa-Grande e Senzala, nas notícias e na hashtag: #justiçapormiguel. - Silva, Fernanda Pinheiro de Souza e (2021)
We experience a distint time in which access to information is increasing every day, and so on, people are able to interact as in no other time, from this interaction several debates are happening on topics never before discussed on a large scale, and one of them is what we will see here in this research: the so-called Brazilian racial democracy as a construct of contemporary racism. The problem that we will observe diachronicly is knowing that racial democracy has been sustained for ideological and political purposes in which way do discursive naturalizations about racial democracy over the years contribute to the naturalization of current racism? The general aim is analyzing discursive naturalizations of Brazilian racial democracy as a mechanism to support contemporary racism. Some of the specific objectives are: 1. Reconstructing the historical context of the Brazilian racial democracy myth; 2. Identify Gilberto Freyre's discursive and ideological position in the CasaGrande & Senzala book related to his defense of Brazilian racial democracy; 3. Prove and reconstruct the media discourses about The Miguel Case related to the racial democracy idea through the Critical theory of Discourses; 4. Analysing the popular discourses through de news comments about the Miguel case and through the hashtags from the same case by the Critical theory of discourse;5. Correlating decolonial and post-colonial studies with the corpora research. According to Fernandes (2007, p.61), Gilberto Freyre systematized the myth of a racial democracy through the ideia of a miscegenation theory. This systematization said by the author is related to the work of Casa-Grande & Senzala, which brings up precisely the issue of racial miscegenation in Brazil in exchange for the valorization of the Brazilian black identity. The same author (2007) discusses the marginal situation of the black today, stating that the destitution of the slave took place in Brazil harshly, it represented the last plunder he suffered, much more than a gift or a concrete opportunity. As stated by Camargo & Ferreira (2011): “It seems to be politically correct to treat Afro-descendants as 'dark'. This euphemism, strongly rooted in Brazilian culture, is a symbolic resource to escape the reality in which discrimination reigns “As blacks constituted, since the colonial period, the majority of the population, and whites a minority, an intermediate category was created, the mulatto, which served as an escape valve for racial tension”. the myth of racial democracy is discussed in society, what we propose as a differential for studies related to the naturalizations of this democracy is the exposure of a view coming from Critical Discourse Analysis (ACD), as stated by Teo (2000) who intends to "unveil the fundamentals ideological discourses that have become so natural over time that we begin to treat them as common, acceptable and natural traits of discourse ".